2019
DOI: 10.1016/j.ijpe.2019.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Firms’ green R&D cooperation behaviour in a supply chain: Technological spillover, power and coordination

Abstract: In response to the global fight against climate change, a growing number of firms cooperate with their supply chain partners on green innovations. This study explores firms' green R&D cooperation behaviour in a two-echelon supply chain in which a manufacturer and a retailer first cooperate to invest green R&D and then organise production according to a wholesale price contract. Through a comparison with non-cooperation models, we evaluate the effects of green R&D cooperation on the economic, environmental and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(88 citation statements)
references
References 38 publications
3
68
0
1
Order By: Relevance
“…us, the carbon abatement investment cost can be given by Retail price of manufacturer i's product Mathematical Problems in Engineering (c 3 e 2 /2). Similar assumptions were made in earlier studies [44][45][46].…”
Section: Assumptionsupporting
confidence: 61%
“…us, the carbon abatement investment cost can be given by Retail price of manufacturer i's product Mathematical Problems in Engineering (c 3 e 2 /2). Similar assumptions were made in earlier studies [44][45][46].…”
Section: Assumptionsupporting
confidence: 61%
“…Their results confirmed that regardless of who has leadership, a hybrid recycling mode outperforms in terms of the overall supply chain profit and recycling performance. Chen et al [52] analyzed green research and development (R&D) cooperation behavior of firms while considering different power structures. They proved that green R&D cooperation between supply chain members has a positive impact on consumer surplus and environmental protection under retailer-led and manufacturer-led supply chains.…”
Section: Power Structuresmentioning
confidence: 99%
“…Wang et al [27] examined the antecedents, consequences, and moderators of fairness perceptions in consumer responses to the offering of green services, and their results revealed that consumers' inference of the firm's relative profit negatively influences their perceived fairness. Recently, Chen et al [28] indicated that the improvement of firms' economic performance resulting from R&D cooperation is mainly determined by firms' own level of green contribution. In addition, Laroche et al [29], Morrison and Beer [30], and Kai and Deng [31] provided empirical support for the growing environmental consciousness of consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To reflect the fact that the consumer preferentially purchases environmentally friendly products, as in Guo et al [15], Chen et al [28], and Agrawal and Uelkue [39], we assume that if a new greener version of the national brand is introduced, then consumers' willingness to pay increases by a factor 1 1 a σ = + , where a represents Suppose that all consumers' willingness to pay for a national brand is v, which is uniformly distributed on the interval [0,1]; that is, v ∼ U[0, 1] [38]. To reflect the fact that the consumer preferentially purchases environmentally friendly products, as in Guo et al [15], Chen et al [28], and Agrawal and Uelkue [39], we assume that if a new greener version of the national brand is introduced, then consumers' willingness to pay increases by a factor σ 1 = 1 + a, where a represents the level of environmental friendliness of the new greener version of the national brand. Thus, following Yin et al [38] and Agrawal and Uelkue [39], we can obtain the consumer utility function for the new greener version of the national brand by solving U n = σ 1 v − p n , where p n refers to the price of the new greener version of the national brand.…”
Section: Assumptionsmentioning
confidence: 99%